SEJARAH DAN AJARAN TAREKAT TIJANIYAH DI BANDUNG BARAT 1930-1970 - Ahmad Faiz Rofi'i (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2023)
Tarekat Tijaniyah is a teaching of Sufism that emerged in the 18th century originating from Al-Jazair. This order was taught by Sheikh Ahmad al-Tijani. The purpose of this study is to find out in detail about the history and teachings of the Tijaniyah Order. The research method used is a qualitative method with a social history approach. The results of this study show that tarekat is one of the ways to get closer to God. Tarekat is also called an institution or organization to accommodate people who want to take a spiritual path with God. One of them is the Tijaniyah order. In its development, this order entered Indonesia in the early 20th century brought by Sheikh Ali bin Abdullah Al-Thayyib. The movement first developed in Taksimalaya, Bogor and Buntet Pesantren Cirebon. As for entering the West Bandung area, it began with the presence of KH Usman Dhamiri and KH Badruzzaman. The teachings introduced by the Tijaniyah tarekat in West Bandung have simple characteristics, namely wirid hailalah, wadzifah and shalawat faith. According to the teachings of the Tijaniyah tarekat, it is considered as one of the solutions to harmonize the life of the world and the hereafter. In addition, to cleanse the human soul to become calm by taking various ways to be practiced so as to achieve the pleasure of Allah SWT.